Optimising detector readout settings for the detection of spatial correlations between SPDC photon-pairs - K. Roberts; T. Gregory; O. Wolley; M. J. Padgett (Scientific Reports)
Abstract SPDC photon-pairs exhibit spatial correlations which can be measured using detector arrays sensitive to single photons. However, these detector arrays have multiple readout modes and in order to optimise detection it is important to select the optimum mode to detect the correlations against a background of optical and electronic noise. These quantum correlations enable applications in imaging, sensing, communication, and optical processing. Here we compare the measurement of spatial correlations for a broad range of readout modes of an EMCCD camera and attempt to characterise the optimal readout mode for our purposes. This assessment is important for the use of detector arrays of different types for use in quantum, low-light, enhanced resolution, imaging systems.